A primary cell-based invitro model of the human small intestine reveals host olfactomedin 4 induction in response to Salmonella Typhimurium infection. (31st December 2023) - Däullary, Thomas; Imdahl, Fabian; Dietrich, Oliver; Hepp, Laura; Krammer, Tobias; Fey, Christina; Neuhaus, Winfried; Metzger, Marco; Vogel, Jörg; Westermann, Alexander J.; Saliba, Antoine-Emmanuel; Zdzieblo, Daniela
ABSTRACT: Infection research largely relies on classical cell culture or mouse models. Despite having delivered invaluable insights into host-pathogen interactions, both have limitations in translating mechanistic principles to human pathologies. Alternatives can be derived from modern Tissue Engineering approaches, allowing the reconstruction of functional tissue models in vitro . Here, we combined a biological extracellular matrix with primary tissue-derived enteroids to establish an in vitro model of the human small intestinal epithelium exhibiting in vivo -like characteristics. Using the foodborne pathogen Salmonella enterica serovar Typhimurium, we demonstrated the applicability of our model to enteric infection research in the human context. Infection assays coupled to spatio-temporal readouts recapitulated the established key steps of epithelial infection by this pathogen in our model. Besides, we detected the upregulation of olfactomedin 4 in infected cells, a hitherto unrecognized aspect of the host response to Salmonella infection. Together, this primary human small intestinal tissue model fills the gap between simplistic cell culture and animal models of infection, and shall prove valuable in uncovering human-specific features of host-pathogen interplay.